PEMETAAN KARAKTERISTIK VISUAL TIPOGRAFI VERNAKULAR PEDAGANG KAKI LIMA DI KOTA BANDUNG - Ira Carella; Naomi Haswanto; Riama Maslan Sihombing (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2017)
Bandung has already become a melting pot of migrant population who come from rural areas, including street vendors society. One distinguishing feature of Bandung's street vendors is its local lettering art, known as vernacular typography. Besides its economic function as a sign to convey information about street vendor's goods, vernacular typography also has a social function to represent the collective identity of street vendors society in Bandung. Collective identity resides in an abstract concept that forms harmony within the diversity in vernacular typography. The aim of this study is to reveal the harmony within diversity in vernacular typography of street vendors in Bandung by systematically assessing its visual characteristics. This study is structured by two continuous steps. The first is synthesizing a mapping method that would be relevant to be applied on vernacular typography. It results in a set of visual aspects with meaning potentials synthesized from van Leeuwen's distinctive features of typography, Machin's inventory of typographical meaning potentials, and Haswanto's morphology of vernacular typography. The second step is assessing vernacular typography samples through content analysis to reveal its visual characteristics. The result suggests that some characteristics are formed by its limited space, materials and processes. Several characteristics tend to create a typical communication system of urban sector informal society in using vernacular typography.